Pengaruh Product Quality dan Promotion Terhadap Trust dan Purchase Decision pada Produk Valizastuff di Shopee - Muhammad Faisal; Parlagutan Silitonga (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the relationship between product quality and promotion on trust and purchasing decisions at the Valizastuff online store in e-commerce. The population in this study were all Valizastuff customers. This study involved 240 respondents who were collected using questionnaire distribution with Accidental Sampling technique. The data analysis method was carried out using Structural Equation Modeling (SEM) with the help of Smart-PLS software (v.3.2.9). The results of this study indicate a significant influence between product quality and promotion on trust and purchasing decisions. The results show a positive and significant direct influence between product quality on trust and purchasing decisions and the results of this study indicate that promotion has a positive and significant influence on trust and purchasing decisions. Trust also has a positive and significant influence on purchasing decisions. Therefore, it is important to maintain consumer trust in an effort to increase purchasing decisions.